Phosphorylated 11S globulins in sunflower seeds - Quiroga, Ivana Yoseli (2013)
Helianthinins are storage proteins present in Helianthus annuus seeds, belonging to the 11S globulin family. Here we describe that a fraction of the helianthinins is phosphorylated. This conclusion is supported by different criteria, including identification by matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry of major protein bands revealed with a specific dye for phosphoproteins, anti-phosphoserine antibody and binding to a phosphoprotein affinity matrix. Moreover, we show that the phosphorylation status of helianthinins changes following germination.